JURIDISTIC REVIEW OF LAW OF COMMUNITY AWARENESS IN ULUNGGOLAKA VILLAGE IN LAND REGISTRATION - Patmasari, Patmasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
This study aims to determine and analyze the legal awareness of the Ulunggolaka community in registering land and to find out and analyze the causal factors so that there are still ulunggolaka urban communities who do not register land. The research method used is empirical legal research that examines primary data obtained from observations, questionnaires, and interviews. The results of this study indicate that the legal awareness of Ulunggolaka Village community in conducting land registration is still relatively low by referring to the answers of respondents who have given their answers based on four legal awareness indicators, namely: (1) Legal Knowledge, (2) Understanding of the law, (3) ) Legal attitude and (4) Pattern of legal behavior. The causal factor so that there are still ulunggolaka urban communities who do not register their land is based on the low legal awareness of the community of the importance of securing assets (land) by obtaining guarantees and legal certainty so that ownership is not strongest and cannot be disturbed, and besides that the community is unable to meet the requirements that must be completed in carrying out land registration, especially proof of the origin of the land, plus the expensive costs and administrative arrangements that are difficult for the community.